A randomized, phase II trial of adjuvant immunotherapy with durable TKI-free survival in patients with chronic phase CML. (December 2021) - Webster, Jonathan A.; Robinson, Tara M.; Blackford, Amanda L.; Warlick, Erica; Ferguson, Anna; Borrello, Ivan; Zahurak, Marianna; Jones, Richard J.; Smith, B. Douglas
Highlights: Adjuvant interferon-α/GM-CSF and K562/G-CSF vaccine were safe with TKIs. Patients more frequently discontinued interferon-α/GM-CSF due to side effects. Adjuvant interferon-α/GM-CSF more frequently led to undetectable BCR-ABL PCR. 36.4 % of patients sustained treatment-free remission after interferon-α/GM-CSF. Abstract: Purpose: Chronic myeloid leukemia (CP-CML) patients can achieve undetectable minimal residual disease (UMRD) and discontinue tyrosine kinase inhibitors (TKIs). Cellular immunity plays an important role in CML disease control. We conducted a randomized, non-blinded phase II trial of adjuvant immunotherapy with TKIs to facilitate TKI discontinuation. Methods: TKI-treated patients with CP-CML were randomized to receive the K562/GM-CSF vaccine (vaccine) OR Interferon-α + Sargramostim (IFN). If UMRD was achieved, then all treatment was stopped. Patients who did not achieve UMRD within one year, had a molecular relapse, or discontinued therapy for toxicity could crossover. Results: Thirty-four patients were randomized to IFN (n = 18) or vaccine (n = 16), and 21 patients crossed over (IFN⟶vaccine: n = 9, vaccine⟶IFN, n = 12). TKIs at enrollment included imatinib (n = 31), nilotinib (n = 2), and dasatinib (n = 1). No patients discontinued vaccine due to side effects, while 33 % of IFN-treated patients discontinued treatment. More patients randomized to IFN (47.4 %, 95 % CI: 16.7–66.7 %) versus vaccine (25.0 %, 95 % CI: 0.5–43.5 %) achieved UMRD within one year. Seven patients randomized to IFN discontinued treatment with 28.6 % (95 % CI: 8.9–92.2 %) sustaining treatment-free remission (TFR) at 1 year, while three patients randomized to vaccine discontinued treatment with none sustaining TFR. Including crossover, there was a cumulative discontinuation success rate of 36.4 % (95 % CI: 16.6 %–79.5 %) after adjuvant IFN. Patients who sustained TFR received a median of 29 months of imatinib prior to discontinuation. Conclusion: Adjuvant IFN led to durable TFRs with limited prior TKI exposure with comparable success to prior discontinuation trials, but many patients stopped IFN early.